Hashtag Moderasi Beragama: A Social Network Analysis - Taufik, Egi Tanadi (Digital Muslim Review, 2025)
This study employs social network analysis to examine the use of hashtags associated with oppositional dialectics in the discourse on religious moderation (moderasi beragama) on Twitter/X. Resistance to and rejection of the state-sponsored moderation discourse have emerged in digital spheres, generating a meta-narrative that amplifies marginalized and dissenting voices. Existing studies on moderasi beragama predominantly focus on ontological frameworks, policy implementation, and high-level state narratives. However, limited attention has been given to how the Ministry of Religious Affairs (MoRA) and other state institutions engage in grassroots conversations, where the discourse is actively contested. This article explores how networked citizens engage with the discourse, forming social networks that either support or critique the state's position. Data were collected and analyzed in three phases in October 2022 using the Netlytic program, focusing on five hashtag cases. The dataset comprises 8,626 uploaders and 15,656 tweets. The findings reveal that the state has largely failed to engage in virtual conversations on moderasi beragama. X has arguably become a digital mausoleum of intellectual discourse, yet while the state-defined concept of moderation is familiar to some, its socialization efforts on social media remain significantly weaker than its high-level consortiums and offline initiatives. The study underscores the urgent need for digitally literate ambassadors of moderasi beragama to counteract narratives of resentment and mitigate the proliferation of conspiratorial theories surrounding the discourse.